Theoretical Bases of the Study of Dialecticisms in the Language of Fiction (Linguostylistic Studies, 2015)
The problem of interaction between literary language and dialects is one of the fundamental theoretical and practical issues of functioning of literary language. In the article theoretical and methodological bases of studying of dialecticisms in artistic literature are conceptualized. The author summarizes the views of scientists at dialecticisms as stylistic category, as historically variable phenomenon and as display of adaptation in literary language of the territorially-differentiated elements. At present dialects are perceived as equal expression of the national language, so they increasingly are subjected literary treatment. In the works of contemporary writers from Polissia various options of interaction between dialects and literary language are traced. Key words: artistic literature, literary language, territorially-differentiated elements, dialecticisms, stylistic functions of the dialecticisms. References